Exploration and Practice of Higher Vocational Education under the Development of Vocational Education Informatization Based on a Case Study of XJ College - Qingjun Liang, Shuie Wang (Forest Chemicals Review)
The reform of higher vocational education continuously puts forward new demands for information construction, such as continuous innovation of technology application and promotion of sustained development of information technology. In turn, the development of information technology promotes the reform of higher vocational education. The two influence and promote each other, forming a circular and spiral upward trend. Moreover, each cycle has further promoted the expansion of informatization connotation of higher vocational education and the continuous improvement of the overall development level at a new starting point. Higher vocational colleges must take into account the level and characteristics of higher vocational education in implementing educational informatization, and explore a high-quality development path with vocational education characteristics, in line with the school situation, effective and continuous improvement through practice.